ChemInform Abstract: Diastereoselective Synthesis of Fused Lactone‐Pyrrolidinones; Application to a Formal Synthesis of (‐)‐Salinosporamide A. Issue 7 (29th January 2015) - Logan, Angus W. J.; Sprague, Simon J.; Foster, Robert W.; Marx, Leo B.; Garzya, Vincenzo; Hallside, Michal S.; Thompson, Amber L.; Burton, Jonathan W.
Abstract A mild methodology is developed for the synthesis of a range of fused bicyclic lactone‐pyrrolidinones.